PENGARUH PEMBERIAN MULSA ALANG-ALANG (Imperata cylindrica) DAN PUPUK UREA, TSP, KCL PADA PERTUMBUHAN DAN PRODUKSI KACANG HIJAU (Phaseolus radiatus L.) - Irene Farida Widawaty; Armaini ' '; Fetmi ' Silvina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
ABSTRACT This study aims to determine the interaction of reed mulch and Urea, TSP, KCl fertilizers and to get the best dose on the growth and yield of mung bean. The research was conducted on August to October 2015 at the Experimental Farm, Faculty of Agriculture, University of Riau, Pekanbaru. This experiment based on factorial, arranged in Completely Randomized Design (CRD) with 2 factors and 3 replications. The first factor are 3 levels mulching reeds (without mulch reeds, mulch reeds 8 ton/ha and 12 ton/ha). The second factor are 3 levels of fertilizer Urea, TSP, KCl (25, 37.5, 25 kg/ha), (37.5, 56.25, 37.5 kg/ha) and (50, 75, 50 kg/ha). Data were analyzed statistically and Duncan's Multiple Range test at 5% level. The results showed that the interaction of mulch reeds and Urea, TSP, KCl had no effect on plant height, number of branches, flowering dates, number of pods per plant, number of pods pithy per plant, yield per plot and weight of 1000 seeds and influential the length of the main stem segments. Based on the research results 12 ton/ha of mulch reeds and 25, 37.5, 25 kg/ha of Urea, TSP, KCl was the best results on the growth and yield of mung beans. Keywords: mung beans, mulch, fertilizers, yield.